2019
DOI: 10.1080/02687038.2019.1602860
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the intensity and comprehensiveness of aphasia services: identification of key factors influencing implementation across six countries

Abstract: M. ORCID: 0000-0001-7344-2262, Pritchard, M. and Le Dorze, Guylaine (2019). Increasing the intensity and comprehensiveness of aphasia services: identification of key factors influencing implementation across six countries. Aphasiology, Increasing the intensity and comprehensiveness of aphasia services:Identification of key factors influencing implementation across six countries. AbstractBackground: Aphasia services are currently faced by increasing evidence for therapy of greater intensity and comprehensivenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 40 publications
1
32
0
1
Order By: Relevance
“…Each factor was considered to act both as a facilitator and barrier, depending on when and to what extent the factor was present. Trebilcock et al (2019) thereby provided additional support to the conclusions drawn earlier by Stephens and Upton. (2012), that lack of time for research, lack of time for implementation, lack of access to resources, and lack of skills in accessing and understanding the research were the primary barriers preventing SLPs from complying with EBP.…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…Each factor was considered to act both as a facilitator and barrier, depending on when and to what extent the factor was present. Trebilcock et al (2019) thereby provided additional support to the conclusions drawn earlier by Stephens and Upton. (2012), that lack of time for research, lack of time for implementation, lack of access to resources, and lack of skills in accessing and understanding the research were the primary barriers preventing SLPs from complying with EBP.…”
Section: Introductionsupporting
confidence: 71%
“…The results further indicated that a large proportion of SLPs and audiologists had limited knowledge of EBP. Trebilcock et al (2019) investigated barriers and facilitating factors for the implementation of intensive and comprehensive aphasia services for PWA among SLPs, and found that environmental context and resources (factors affecting a situation/circumstance or a physical environment), beliefs about consequences (presumed outcomes of a caring effort), professional role and identity (personal or professional characteristics and/or behaviors), skills (level of skill in operating) and knowledge (knowledge of a condition, treatment, or environment) impacted the implementation of the services. Each factor was considered to act both as a facilitator and barrier, depending on when and to what extent the factor was present.…”
Section: Introductionmentioning
confidence: 99%
“…There remains however a lack of consensus and high‐quality guidance around the optimum approach to aphasia rehabilitation, for example in relation to goal setting, counselling and patient/caregiver support, and this may impact on care quality and consistency (Brady et al., 2013; CCRE in Aphasia Rehabilitation, 2014; Rohde, Worrall, & Le Dorze, 2013; Shrubsole, Worrall, Power, & O’Connor, 2017). This evidence gap is compounded by an evidence‐practice gap including the provision of aphasia‐friendly information, support with depression and SLT of adequate intensity to maximise effectiveness (Code & Petheram, 2011; Foster, Worrall, Rose, & O'Halloran, 2015; Hickey, Shrubsole, Worrall, & Power, 2019; Hilari et al., 2015; Rose, Worrall, McKenna, Hickson, & Hoffmann, 2009; Shrubsole, Worrall, & Power, 2019; Shrubsole, Worrall, Power, & O'Connor, 2018; Thomas et al., 2013; Trebilcock et al., 2019). Surveys of SLTs in Australia and Hong Kong highlighted that PWA received sub‐optimum dosage for effective therapy (Kong, 2011; Kong & Tse, 2018; Rose, Ferguson, Power, Togher, & Worrall, 2014; Verna, Davidson, & Rose, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Though one article elicited views of clinicians delivering ICAPs [144] and another explored clinicians' views on experienced and perceived barriers to ICAP implementation [161], the literature provides no qualitative data from PWA or significant others about the perceived value of ICAPs. It is crucial to access the insights, lived experience, and expertise of PWA, their families, and key stakeholders in intervention design and this process is a recommended key stage in the development of a complex intervention [162,163].…”
Section: Lack Of Qualitative Datamentioning
confidence: 99%